Improved biosafety of a lentiviral vector by reducing cellular gene activation. (23rd April 2019) - Song, Li; He, Jiaping; Gao, Yue; Fang, Yudan; Zhang, Liping; Wang, Juan; Sun, Fengqiang; Zhang, Fan; Zeng, Yitao; Zeng, Fanyi; Zhang, Jingzhi
Abstract: Background: Lentiviral vectors (LVs) have enhancer activity and/or transcriptional read‐through (EATRT) properties that can lead to the activation of adjacent genes. Consequently, patients may be at increased risk for adverse effects if such vectors are used clinically. Methods: In the present study, we assessed the abilities of different "pro‐LV"‐like constructs with respect to decreasing its EATRT, including the "pro‐LV" vector bearing a chimeric ΔLTR of the human foamy virus R‐U5 region replaced by that of an LV (HF). Results: By analyzing the EATRT of "pro‐LV" constructs transfected in 293T cells, we observed that the inclusion of the first 400 bp of the chicken β‐globin locus HS4 insulator core sequence oriented in the reverse direction (C–) combined with two copies of the simian virus 40 upstream‐sequence element (U) at the ΔU3 of ΔLTR region of "pro‐LV" tended to shield the adjacent genomic sequences, such that the EATRT rate was lower than when either of the C– or U was included in the "pro‐LV". Moreover, upon transduction, the pro‐HF appears to reduce the EATRT rate in the chromosomes of 293T (by 80%) and human peripheral blood mononuclear cells (PBMCs) (by 75%) compared to when pro‐LV C–U was included (with a 60% and 89% reduction in 293T and PBMCs, respectively). The HF construct had a significant reduction of viral biological titer compared tiowhen the pro‐LV C–U was used in 293T cells. Conclusions: The results of the present study provide an important basis for the clinical applicability of LVs in gene and cell therapy.